Bridging Classical Arabic Rhetoric and Cognitive Linguistics: A Systematic Review of Kinayah and Conceptual Metaphor Theory - Yusuf Ali Tantowi; Syihabuddin Syihabuddin; Dadang Sudana; Mohamed Mohamed Emam Dawood (UIN Sunan Gunung Djati Bandung, 2025)
Descriptive classical balaghah approaches have dominated figurative studies in the Qur'an. In its development, Qur'anic studies have begun to utilise cognitive linguistic approaches, albeit to a limited extent. These two approaches have not been systematically integrated, even though they share a common vision in understanding indirect meaning. This study aims to map the integration of the concept of Kināyah in classical balaghah with the conceptual metaphor theory (CMT) framework in Qur'anic linguistic studies through a systematic literature review. Following the PRISMA 2020 protocol and searching for data from the Scopus database, 15 articles were obtained that met the inclusion criteria and became the object of analysis. The findings show that studies discussing kinayah and CMT in the Qur'an are still scattered and partial. The characteristics of the definition and classification of kinayah refer to classical, pragmatic, and contextual semantic approaches. CMT is applied variably to explain abstract concepts in the Qur'an through metaphorical mapping, both in eschatological and theological themes, as well as in social discourse. The main challenges in integrating these two approaches include epistemological and terminological differences, as well as linguistic and cultural gaps. However, the opportunities for integration appear promising, especially at the textual and semantic analysis levels through a hybrid approach. This study emphasises the importance of developing an interdisciplinary methodological framework based on kinayah-CMT in Qur'anic linguistic studies. These findings reinforce linguistic-interpretation epistemology, advance adaptive models for Qur’anic figurative analysis, and open new directions for interdisciplinary Qur’anic studies in the digital age.